Analysis Of The Effect Of Green Economy Implementation And Csr Disclosure On The Company's Stock Return In One Of The Sectors Listed On The Indonesia Stock Exchange - Indri Ayu Tansar; Tri Ningsih (LPPM STMIK Mardira Indonesia, 2025)
This study aims to see how the green economy and corporate social responsibility (CSR) disclosure affect the company's stock returns in one of the sectors listed on the Indonesia Stock Exchange between 2021 and 2024. This research is a follow-up to the previous research that examined the impact of Covid 19 on stock returns and trading volume at PT Garuda Indonesia, Tbk. The data used in this study is secondary data in the form of annual reports from 23 transportation sector companies listed on the Indonesia Stock Exchange which were selected through purposive sampling techniques. In this study, a linear regression method of panel data and a data analysis tool in the form of Eviews 9 were used. The free variables are the green economy and CSR while the bound variable is stock returns. Other control variables in this study are company size (Total Assets) and profitability (Return on Equity). The results show that there is partially insufficient statistical evidence to state that the green economy, which is measured as a dummy variable (1 = listing environmental costs, 0 = no), has a significant effect on stock returns, while CSR disclosures have a significant effect on stock returns. In addition, the ROE and Total asset control variables do not significantly affect stock returns. This research is expected to provide information for companies in making policies for the implementation of the green economy and CSR disclosure in relation to stock returns.